Hydroxyurea as A Therapeutic Approach in Transfusion-dependent Thalassemia - Rudy Afriant; Talsi Transino (CV. AKBAR PUTRA MANDIRI, 2026)
Major thalassemia, or transfusion-dependent thalassemia (TDT), is a severe form of hemoglobin disorder that requires a lifetime regular blood transfusion. Longterm transfusion leads to iron overload that damaging vital organs and increasing morbidity and mortality. Therefore, alternative therapies are needed to reduce transfusion frequency and its complications. Hydroxyurea (HU) is currently being studied for its potential benefit in TDT. Hydroxyurea is an antimetabolite and antineoplastic agent for sickle cell disease. Hydroxyurea induces the production of fetal hemoglobin (HbF) by stimulating γ-globin expression and inhibiting ribonucleotide reductase, which is essential in DNA synthesis, thereby suppressing ineffective erythropoiesis. This pharmacological effect may increase total hemoglobin levels and reduce transfusion requirements in TDT. Hydroxyurea also improves erythropoiesis, decreases ferritin levels, and enhances red blood cell morphology. Meta-analyses indicate that approximately 25–60% of patients experience at least 50% reduction in transfusion needs, with mild and reversible adverse events. While it is not recognized as standard therapy, current studies support the efficacy and safety of hydroxyurea as an adjunctive therapy for TDT, particularly in resource-limited settings in developing countries. Further studies are needed to confirm its long-term safety profile and to identify the patient populations most likely to benefit from this therapy.